Differences in Social Support for Pregnant Women between Family Planning and Non-Family Planning - Artur Natalino Corte Real Araújo; Etelvina José Soares Tilman; Eugenia Carvalho de Araújo; Rafael dos Santos Ximenes; Maria Jose de J.C.Alves (PT. Banjarese Pacific Indonesia, 2025)
This study aims to analyze the differences in social support received by pregnant women who participate in the Family Planning (FP) program compared to pregnant women who do not participate in the program. The method used is a systematic literature review, which includes data collection and analysis from various studies related to social support for pregnant women. the results of the study indicate that pregnant women involved in the family planning program receive stronger social support from family, friends, and health workers. this support includes better emotional, informational, and instrumental aspects, which have a positive impact on their mental and physical health. in contrast, non-family planning pregnant women tend to experience social isolation and have limited access to health resources and information. the discussion in this study emphasizes the importance of social support in improving the welfare of pregnant women and the role of the family planning program as a platform to strengthen social support networks. the conclusion of this study shows that better social support in pregnant women who participate in the family planning program contributes to better mental health, lower stress levels, and increase their self-confidence during pregnancy. therefore, it is important to improve the integration of social support in the family planning program to create a more supportive environment for pregnant women, so that they can go through their pregnancy more healthily and optimally.